Beyond National Narratives: A Relational Method for Diasporic Literatures Grounded in Francophone Canada - Poliquin, Laurent (International Journal of Language and Literary Studies, 2025)
This article asks how to read African diasporic writing in French in Canada without forcing it into national boxes. It reframes the old idea that “one people, one territory, one language” should define literature as a habit that can hide what texts actually do on the page. I propose a simple toolkit of six questions to guide analysis: How does the text create contact across difference? How does the city shape scenes and pace? How do past, present, and hoped-for futures overlap? To whom does the voice speak, and how does it hold more than one audience? How do spoken forms like a proverb or a chant become a written rhythm? How do civic and religious worlds share a scene? Three readings model the approach: Didier Leclair writes the migratory city through thresholds, transit, and offices; Monia Mazigh builds ethical address across civic and faith publics; Guy Armel Bayegnak turns cadence, meaningful objects, and mixed codes into structure. A synthesis shows translation on the page working as a method, and “public-making” as a measure of literary form in minor settings. The article offers a clear, portable way to name how texts build relations beyond national narratives. Although grounded in francophone Canada, the method is designed to travel and can inform the analysis of diasporic and minor literatures worldwide.